Generalized Minimax Programming with Nondifferentiable (G, β)-Invexity - D. H. Yuan; X. L. Liu (Journal of Applied Mathematics)
We consider the generalized minimax programming problem (P) in which functions are locally Lipschitz (G, β)-invex. Not only G-sufficient but also G-necessary optimality conditions are established for problem (P). With G-necessary optimality conditions and (G, β)-invexity on hand, we construct dual problem (DI) for the primal one (P) and prove duality results between problems (P) and (DI). These results extend several known results to a wider class of programs.